EPILEPSY OF AGING: AN INCREASING CHALLENGE OF THE 21ST CENTURY - Ristić, Aleksandar; Pejović, Aleksa (Medicinski podmladak, 2024)
Epilepsy in the elderly stands as the third most prevalent serious neurological condition among the older population, trailing only stroke and dementia. Approximately 15,000 individuals live with this condition in the Republic of Serbia. Despite its significance, accurate diagnosis is often hindered by various factors, leading to a perplexing scenario where it is both underrecognized and overdiagnosed. Atypical presentations of epilepsy in the elderly are frequent while the contribution of EEG diagnostics is limited by its modest sensitivity and specificity. Effective management entails prompt evaluation, precise diagnosis, initiation of suitable therapy, patient education, and comprehensive support. The ultimate aim of antiepileptic treatment is to enable patients to resume a normal lifestyle by suppressing seizures without adverse effects. Remarkably, around 80% of patients achieve steady remission with low to moderate doses of antiepileptic drugs in monotherapy. Notably, epilepsy in the elderly significantly elevates mortality, tripling the mortality rate compared to peers without epilepsy.
Keywords: 65 years; seizures; epidemiology; diagnosis; treatment